(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
The constitutional principle of equality not only allows the traditional interpretation of outlawing any kind of discrimination, but could also be interpreted in a more substantial way, having the positive function of reverting unequal conditions. In the sphere of criminal law the latter interpretation demands, on one hand, recognizing the criminal system’s selectivity as an intrinsic characteristic of itself, on the other hand, the existence of a plethora of structural inequalities on the social front, that entails deprival of the use or enjoyment of economic, social and cultural rights. The broader interpretation of the constitutional principle of equality outlined above favors the interpretation of the infra-constitutional article 41.2 from Argentina’s criminal code, with the extent that criminal dogmatics assigns to the concept of culpability due to vulnerability. This legal concept, understood as the implementation of the constitutional principle of equality in criminal matters, determines that the accusations to whom had committed an offense could never include conditions determined by their own state of vulnerability, for which the accused does not bear any criminal responsibility.